2018
DOI: 10.1111/1759-7714.12796
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the number of negative lymph nodes in esophageal carcinoma without lymphatic metastasis

Abstract: BackgroundThe impact of the number of negative lymph nodes (LNs) on survival in patients with esophageal cancer remains a controversial issue. This study investigated the association between the number of resected LNs and the prognosis of patients with node‐negative esophageal carcinoma.MethodsA retrospective review was performed of the data of 429 patients who underwent esophagectomy with modern two‐field lymphadenectomy for the treatment of esophageal cancer between January 1998 and December 2008. Histopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
1
15
1
Order By: Relevance
“…In the present study, a robust five-gene signature to predict the prognosis of patients with ESCC was constructed and validated. However, additional confounding factors should also be considered, including the number of negative lymph nodes (22), metabolic tumor volume, total lesion glycolysis, regional lymph node metastasis and concurrent chemotherapy (23). Furthermore, the included data were limited to two databases, thus the impact of these confounding factors could not be fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a robust five-gene signature to predict the prognosis of patients with ESCC was constructed and validated. However, additional confounding factors should also be considered, including the number of negative lymph nodes (22), metabolic tumor volume, total lesion glycolysis, regional lymph node metastasis and concurrent chemotherapy (23). Furthermore, the included data were limited to two databases, thus the impact of these confounding factors could not be fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated that NLNs count was an advantageous prognostic indicator in lymph node-positive EC patients but not in those who were lymph node-negative [13]. Wu et al [14] draw the conclusion that the number of NLNs was an independent prognostic factor for node-negative EC through a retrospective review of 429 EC patients who underwent modern two-field lymphadenectomy. These results are controversial and need to be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Esophageal cancer is ranked as one of the most common digestive system cancers worldwide and as the seventh most frequent cause of cancer‐related death for males in the United States …”
Section: Introductionmentioning
confidence: 99%